Indoor air quality management system based on industrial code of practice on indoor air quality 2010 - Muhammad Nor Aiman, Yusof (2018)
Health disease related to indoor air quality such as sick building syndrome is believed to cause a low performance of building occupants. Proper management of indoor air quality according to established code of practice can prevent the exposure to indoor air contaminants which will result in IAQ health related diseases. The Industrial Code of Practice on Indoor Air Quality 2010 provides guidance for managing indoor air quality problem and set the minimum standard for the selected IAQ parameters. It is believed that most of the industries already recognized the standard but unavailability of effective technique had delay the implementation of this standard. This research study is conducted to introduce a systematic technique manage indoor air quality problem in industries to achieve acceptable level of indoor air as well as to prevent the presence of sick building syndrome and other IAQ related health disease. This study covered analysis of requirements of the code of practice, development of framework and database management system as well as concept validation through case study from real data of an industry building. Implementation of this technique will help employer to control the presence of indoor air contaminants and minimize the case of IAQ related health disease.